Women's Leadership Style and Work Discipline On The Performance Of Ship Boys: Study On Ship Crew With Female Searers - Mochamad Imroni Mubin; Andy Wahyu Hermanto (Nama Jurnal Akmi, 2023)
This study aimed to determine and analyze: 1) the effect of female leadership style on work discipline, 2) the effect of female leadership style on performance, and 3) how discipline at work affects performance. This kind of research uses a quantitative causal associative survey methodology. In the study, This sampling technique used saturation because all members of the population were sampled as many as 60 ship crews where there was a female leader. This study focused on ship crews with female officers and leaders in the deck department and the engine department, which together had a total of 60 persons. The results showed 1) leadership style has a significant effect on work discipline, 2) women's leadership style has a substantial impact on performance, and 3) work discipline has a significant effect on performance.